Structural Policies in Developing Countries - Borensztein, Eduardo (Washington, D.C. : International Monetary Fund, 1994)
This paper discusses the broad orientation of the economic systems adopted in developing countries. While government-led development strategies were widely followed by developing countries since the 1950s and 1960s, a distinct trend towards the adoption of market-oriented systems has developed in the last decade. The paper reviews international trade policies, noting the move away from protectionism, and financial markets policies, where financial repression is also giving way to more liberal systems. The paper also discusses newer ideas supporting 'industrial policies' or policies to promote certain export activities, that are partly inspired by the success of several East Asian economies, and observes that their application to other developing countries would not be promising.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet